The future of transportation : from electric cars to jet packs - Klepeis, Alicia, 1971- (Capstone Press, 2020)
"Human transportation has come a long way since the invention of the wheel. Vehicles of all sorts have us speeding across land, through water, and in the skies. What might be next? From self-driving cars to jet packs, readers will discover exciting new ways they may get around in the future"--
Includes bibliographical references and index.
Ages 8-11.
Grades 4-6.
Keywords: Transportation -- Forecasting -- Juvenile literature; Transportation -- Technological innovations -- Juvenile literature